An alternative pathway for sweet sensation: possible mechanisms and physiological relevance - Molitor, Elena von; Riedel, Katja; Krohn, Michael; Rudolf, Rüdiger; Hafner, Mathias; Cesetti, Tiziana (Pflügers Archiv, 2020)
Sweet substances are detected by taste-bud cells upon binding to the sweet-taste receptor, a T1R2/T1R3 heterodimeric G protein-coupled receptor. In addition, experiments with mouse models lacking the sweet-taste receptor or its downstream signaling components led to the proposal of a parallel “alternative pathway” that may serve as metabolic sensor and energy regulator. Indeed, these mice showed residual nerve responses and behavioral attraction to sugars and oligosaccharides but not to artificial sweeteners. In analogy to pancreatic β cells, such alternative mechanism, to sense glucose in sweet-sensitive taste cells, might involve glucose transporters and KATP channels. Their activation may induce depolarization-dependent Ca2+ signals and release of GLP-1, which binds to its receptors on intragemmal nerve fibers. Via unknown neuronal and/or endocrine mechanisms, this pathway may contribute to both, behavioral attraction and/or induction of cephalic-phase insulin release upon oral sweet stimulation. Here, we critically review the evidence for a parallel sweet-sensitive pathway, involved signaling mechanisms, neural processing, interactions with endocrine hormonal mechanisms, and its sensitivity to different stimuli. Finally, we propose its physiological role in detecting the energy content of food and preparing for digestion.